Whipple's disease review, prevalence, mortality, and characteristics in the United States: A cross-sectional national inpatient study. Issue 49 (9th December 2022) - Ahmad, Akram I.; Wikholm, Colin; Pothoulakis, Ioannis; Caplan, Claire; Lee, Arielle; Buchanan, Faith; Kyoo Cho, Won
Abstract : Whipple's disease is a rare multiorgan systemic disease caused by Tropheryma whipplei infection that may present with a wide range of signs and symptoms. This study aim to comprehensively review and determine the inpatient prevalence, mortality, risk factors, and reasons for hospitalization of patients with Whipple's disease. ICD-10 codes were used to identify admissions with Whipple's disease during the years 2016 to 2018. Characteristics of admissions with and without Whipple's disease were compared. The most common reasons for hospitalization were identified in admissions with Whipple's disease. The prevalence of Whipple's disease was 4.6 per 1 million hospitalizations during the study period. Whipple's disease admissions were significantly older than other hospitalizations, with a mean age of 60.2 ± 1.6 years compared to 50.0 ± 0.1. Males were more likely to have Whipple's disease and represented approximately two-thirds of hospitalizations. A disproportionate number of admissions occurred in the Midwest. Patients with Whipple's disease were most commonly admitted for gastrointestinal disease, followed by systemic infection, cardiovascular/circulatory disease, musculoskeletal disease, respiratory disease, and neurological disease. High mortality was seen in admissions for central nervous system (CNS) disease. Whipple's disease has heterogeneous presentations for inpatient admissions, and disproportionately affects older males. High hospitalization rates in the Midwest support environmental and occupational disease transmission likely from the soil. Hospitalists should be aware of the various acute, subacute, and chronic presentations of this disease, and that acute presentations may be more common in the inpatient setting.